New Light on the Sufferings and the Burial of the Turin Shroud Man - Matteo Bevilacqua; Giulio Fanti; Michele D'Arienzo (Open Journal of Trauma - Peertechz Publications, 2017)
This paper presents news concerning the transportation of the whole cross on the shoulders and the falling mode of the Turin Shroud (TS) Man on the ground that explains the detected traumas. These news base themselves on the hypothesis that the TS Man is Jesus of Nazareth. Based on historical information and on a structural analysis, after a reconstruction of the Roman "Tau" cross, a life-size sample of it has been built in order to study its compatibility with some traumas visible on the TS. Also discussed are the medical implications caused by a violent blunt trauma from behind, to the neck, chest and right shoulder including the etio-pathogenesis of the head posture of Jesus on the cross represented in traditional iconography. Finally, additional news is included regarding bloodstains like the "blood belt", the "mattress" of spices and the sudarium used as chin bandage.